Neopterin as an Inflammatory Biomarker in Patients with Non-alcoholic Fatty Liver Disease - Ratha, Rawa; Esmail, Vian Ahmed Wasta; Maarouf, Fenk Bakir; Omer, Hemn Abdalla; Al-Nimer, Marwan; Mohammed, Mohammed Omer (Sulaimani Journal for Pure and Applied Sciences, 2022)
Background: Early diagnosis of non-alcoholic fatty liver diseases (NAFLD) through detection of a new biomarker is crucial to prevent disease deterioration. Aim: To evaluate the serum level of neopterin in NAFLD patients and to demonstrate its role as an early biomarker of NAFLD. Methodology: This is an observational, cross-sectional study that conducted on 71 newly diagnosed NAFLD patients and 60 healthy individuals as a control group. Liver enzymes (alanine aminotransferase [ALT] and aspartate aminotransferase [AST]) and uric acid were determined. The serum level of neopterin was measured by ELISA and WBC differential count by a Coulter counter analyzer. Erythrocyte sedimentation rate (ESR) was determined by Wintrobe’s method. Results: NAFLD patients had a significantly higher BMI, waist circumference, and body weight compared to control, also their blood pressure was significantly higher. The serum level of ALT, AST, and uric acid were significantly higher in NAFLD patients than the control. There is non-significant difference between NAFLD patients and controls regarding ESR, lymphocytes and granulocytes, while monocytes and neopterin values were significantly higher among NAFLD patients. Conclusions: Serum neopterin level can be a predictor inflammatory marker in NAFLD patients. Clinical Pharmacists as part of healthcare professionals can support NAFLD patients by educating them on lifestyle modification if the disease is diagnosed early before reaching a critical stage.
Keywords: Nonalcoholic fatty liver disease; pro.inflammatory cytokines; neopterin; cross.sectional study